Experimental Measurements and Correlations Isobaric Vapor-Liquid Equilibria for Water ＋ Acetic Acid ＋ Sec-butyl Acetate at 101.3 kPa - 李玲 贺勇 吴燕翔 邹文虎 (Chinese journal of chemical engineering, 2013)
Isobaric vapor-liquid equilibrium（VLE） data for acetic acid ＋ sec-butyl acetate and water ＋ acetic acid ＋ sec-butyl acetate systems were determined at 101.3 kPa using a modified Rose type. The nonideality of the vapor phase caused by the association of the acetic acid was corrected by the chemical theory and Hayden-O＇Connell method. Thermodynamic consistency was tested for the binary VLE data. The experimental data were correlated successfully with the Non-Random Two Liquids （NRTL） model. The Root Mean Square Deviation （RMSD） of the ternary system was 0.0038. The saturation vapor pressure of sec-butyl acetate at 329 to 385 K was measured by means of two connected equilibrium cells. The vapor pressures of water and sec-butyl acetate were correlated with the Antoine equation. The binary interaction parameters and the ternary VLE data were obtained from this work.